Penerapan Pembuatan Desain Logo dengan Corel Draw pada Siswa SMK Handayani Makassar (STMIK Dharmapala Riau, 2022)
This service activity has a long-term goal to realize SMK Handayani Makassar students who have knowledge and creativity in the computer field, especially for design applications. The short-term goal is to educate students in using tools in graphic design applications, namely Corel Draw, so that students are expected to be able to design and develop students' creative talents in the field of design. This activity was carried out with a comprehensive mentoring method to students of SMK Handayani Makassar through socialization of graphic design applications, using the Corel Draw application. The final output that will be achieved from this activity is an increase in students' ability to use computers as a tool for developing student creativity in the field of design. In addition, students have a guide to using the Corel Draw application to help students use tools and develop into image designs or logo creation. Scientifically, the ultimate goal in this service activity is to publish the results of this service in service journals or mass media publications.